2023
DOI: 10.1039/d3se00495c
|View full text |Cite|
|
Sign up to set email alerts
|

A polypyrrole derived nitrogen doped porous carbon support for an atomically dispersed Mn electrocatalyst for the oxygen reduction reaction

Sanjit Kumar Parida,
Tulasi Barik,
Hrudananda Jena

Abstract: Platinum group metal (PGM)-free catalysts are highly desirable for the oxygen reduction reaction (ORR) in electrochemical energy conversion devices, for large scale commercialization of the technology. Here, we report a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…6−8 A plethora of works have been carried out toward this approach involving nonprecious metal cations stabilized by nitrogen atoms in a porphyrin type environment. This has led to the development of SACs of 3d transition metals (Fe, 9−11 Co, 12−14 Mn, 15,16 Cu, 17 etc.) and p-block elements such as Sn, 18 Sb, 19 and Se 20 as well, primarily serving as potential candidates in electrochemical applications.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6−8 A plethora of works have been carried out toward this approach involving nonprecious metal cations stabilized by nitrogen atoms in a porphyrin type environment. This has led to the development of SACs of 3d transition metals (Fe, 9−11 Co, 12−14 Mn, 15,16 Cu, 17 etc.) and p-block elements such as Sn, 18 Sb, 19 and Se 20 as well, primarily serving as potential candidates in electrochemical applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Design of efficient and cost-effective platinum group metal (PGM)-free electrocatalysts to boost the otherwise sluggish kinetics of oxygen reduction reaction (ORR) is a key challenge in energy storage and conversion devices. Many catalyst design attempts have been made recently toward low-cost alternatives. , One of the attempts to replace PGMs has brought about a new class of bioinspired catalysts called single-atom catalysts (SACs) which consist of atomically dispersed metal centers coordinated to nitrogen atoms on a partially graphitized carbon support (MNxCy or M–N–C). A plethora of works have been carried out toward this approach involving nonprecious metal cations stabilized by nitrogen atoms in a porphyrin type environment. This has led to the development of SACs of 3d transition metals (Fe, Co, Mn, , Cu, etc.) and p-block elements such as Sn, Sb, and Se as well, primarily serving as potential candidates in electrochemical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, metal- and nitrogen-doped carbon materials (M–N–Cs) have been widely studied as potential alternatives to PGMs for ORR electrocatalysis, especially with Fe–N–Cs and Co–N–Cs exhibiting ORR currents that are comparable to those of PGMs in alkaline medium. Less commonly investigated, yet significant to this study, Cr–N–C and Mn–N–Cs have also been shown to offer promising ORR activity. Due to the highly complex structures of these amorphous carbon materials, density functional theory (DFT) is a crucial tool for extracting atomic-level insights on the single atom sites . While the specific coordination can vary across different materials, there is a general consensus that the nature-inspired MN 4 sites are responsible for the observed electrochemical activities .…”
Section: Introductionmentioning
confidence: 99%
“…Intensive investigation in this arena has yielded various nonprecious metals (NPMs) and metal-free materials as potential alternatives . Compounds of transition metals such as oxides, nitrides, sulfides, phosphides, hydroxides, etc., despite catalyzing the ORR in alkaline medium, still require improvement in their activity, stability, and utilization efficiency. , As another alternative, metal–nitrogen–carbon-based electrocatalysts with isolated single atoms of transition and p-block elements coordinated to N atoms have emerged as potential candidates for the ORR. Although this class of catalysts, also called single-atom catalysts (SACs), has demonstrated excellent ORR activity, it still suffers from limited stability due to the demetalation of metal atoms from the active sites and the restricted utilization of the M–N–C active centers due to the lack of adequate porosity. The demetalation issue also persists in alkaline medium under ORR condition …”
Section: Introductionmentioning
confidence: 99%